Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18006/2018.6(5).782.791
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endophytic Bacteria With Plant Growth Promoting Activities Isolated From Six Medicinal Plants

Abstract: The present investigation aimed to isolate and characterize endophytic bacteria from six selected medicinal plants (Ocimum sanctum, Aegle marmelos, Cinnamomum cassia, Azadirachta indica, Calotropis procera and Rauwolfia serpentina) with plant growth promoting activities. Total 38 endophytic bacteria were isolated from the studied plant species by following standard microbiological culture methods. All the isolated bacteria were screened for the production of hydrolyzing enzyme and result of study revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…The phenomenon of solubilization of potassium from soil by endophytic microbes mostly dependent on the pH and type of soil [18] . Endophytic bacteria belonging to genera Achromobacter, Acinetobacter, Bacillus, Burkholderia [19,20,22,32] have been reported for potassium-solubilization. In the present study, three among fourteen isolates were able to solubilize potassium by showing zone of solubilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of solubilization of potassium from soil by endophytic microbes mostly dependent on the pH and type of soil [18] . Endophytic bacteria belonging to genera Achromobacter, Acinetobacter, Bacillus, Burkholderia [19,20,22,32] have been reported for potassium-solubilization. In the present study, three among fourteen isolates were able to solubilize potassium by showing zone of solubilization.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, three among fourteen isolates were able to solubilize potassium by showing zone of solubilization. In previous studies, Bacillus licheniformis and Pseudomonas azotoformans which were isolated from the soil of rice plants, using two potassium solubilizing bacteria, could increase the availability of potassium in the soil [20] . Another study concluded that among all investigated Actinobacteria strains; Streptomyces alboviridis, Streptomyces griseorubens and Nocardiopsis Alba were able to solubilize potassium [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial activity of the pigment was studied following Panigrahi et al, 2018. Six pathogens namely, Escherichiacoli MTCC 723, Pseudomon asaureus MTCC 741, Vibrio cholerae MTCC 3906, Staphylococcus aureus MTCC 902, Klebsiella pneumoniae MTCC109 and Enterococcus cloacae MTCC 7322 were used.…”
Section: Dpph Scavenging Rate (%) = {1-(a 517 Sample -A 517 Control)/...mentioning
confidence: 99%
“…Considering this, an array of sustainable agricultural practices involving soil microbiota and endophytes are being suggested for a stable enhancement in plant health and productivity (Lucy et al, 2004;Arcand and Schneider, 2006). Among all the classes of microbes which have beneficial interactions with plant, the endophytes have gained special interest (Kobayashi and Palumbo, 2000;Dudeja et al, 2012;Panigrahi et al, 2018) as these microorganisms are not only critical for promoting plant growth and productivity (Kloepper and Schroth, 1981), but having a specialized niche within the plant tissues, they act as biocontrol agents (Mercado--Blanco and Bakker, 2007;Ryan et al, 2008). The colonizing capabilities and persistency of these microbes determines their resilience and diversity within the plant and in nature respectively (Rosenblueth and Martínez-Romero, 2006).…”
Section: Introductionmentioning
confidence: 99%